Redes globales de acción contra la mundialización neoliberal. El ciclo de protesta 1998 - 2003 - Cardona Hansen, Fernando (Sociedad y Economía, 2005)
A cycle of global protest started in May 1998. Massive movements and direct actions against the more visible agents of the economic globalization process were observed in different cities and countries of the world, either through vast displacements of activists to cities or through the coordination of simultaneous global autonomous actions in different places and hemispheres. This set of collective actions is supported by social networks of dissidents who, since the middle of the 1990s, are articulated to processes of convergence and exchange of experiences that serve to construct the social struggle against globalization. Along with the appropriation and intensive use of the electronic communication, a platform of actions has been constructed to confront in a coordinated manner governments and supranational institutions that promote policies of free exchange, using as their main weapon the direct action and civil disobedience